Analisis Pengaruh Ketimpangan Gender Terhadap Pertumbuhan Ekonomi Di Sulawesi Selatan - Qarina, Qarina; Wahab, Abdul (ICOR: Journal of Regional Economics, 2022)
This study aims to determine whether the components of the Gender Development Index (GPA) such as the ratio of inequality in life expectancy, the ratio of the average length of school and the ratio of the labor force participation rate have an effect on economic growth in South Sulawesi Province. This research uses quantitative research. The data processing technique uses multiple linear regression through the SPSS 24 program. The data used is secondary data with the type of time series data, derived from historical records or reports arranged in published and unpublished archives. The results of this study indicate that the inequality ratio of life expectancy is not significant and has a negative effect on economic growth, while the inequality ratio of the average length of schooling has a significant and negative effect on economic growth, and lastly, the inequality ratio of the labor force participation rate is significant and has a positive effect on growth. economy in South Sulawesi. Simultaneously, the three X variables have an effect on economic growth. This research is expected to be a reference for the government to take appropriate and good solutions to solve problems related to gender inequality in South Sulawesi.